Recurrent SARS-CoV-2 infections and their potential risk to public health - a systematic review. - Seth Kofi Abrokwa; Sophie Alice Müller; Alba Méndez-Brito; Johanna Hanefeld; Charbel El Bcheraoui (PLoS ONE)
Objective To inform quarantine and contact-tracing policies concerning re-positive cases-cases testing positive among those recovered. Materials and methods We systematically reviewed and appraised relevant literature from PubMed and Embase for the extent of re-positive cases and their epidemiological characteristics. Results In 90 case reports/series, a total of 276 re-positive cases were found. Among confirmed reinfections, 50% occurred within 90 days from recovery. Four reports related onward transmission. In thirty-five observational studies, rate of re-positives ranged from zero to 50% with no onward transmissions reported. In eight reviews, pooled recurrence rate ranged from 12% to 17.7%. Probability of re-positive increased with several factors. Conclusion Recurrence of a positive SARS-CoV-2 test is commonly reported within the first weeks following recovery from a first infection.